Consumer Satisfaction on Local Instant Noodles with Japanese Identity in Semarang - Meier, Auretta M.; Ayyub, Ichlasul (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
The global fusion of cultures has led local brands to adopt foreign identities for marketing appeal. This study examines Semarangâ€™s consumersâ€™ satisfaction with two instant noodle products â€“ a local brand (Indomie Premium Japanese Curry) adopting Japanese identity and a genuine Japanese brand (Nissin Ramen). It addresses how consumer ethnocentrism influences satisfaction. A purposive sample of Semarang consumers (age â‰¥16) who recently purchased both products was surveyed online. Reliability and validity of the CSI (Customer Satisfaction Index) and CETSCALE (Consumer Ethnocentrism Scale) instruments were confirmed (Cronbachâ€™s Î± >0.67 for all scales). Importance-Performance Analysis (IPA) identified key product attributes (packaging, taste, price, availability, â€œJapanese ambienceâ€) and computed CSI values. Indomie yielded a CSI of 78.20% and Nissin 76.32%, both in the â€œsatisfiedâ€ category. Regression analysis revealed that higher ethnocentrism modestly increased satisfaction for both products (Î²â‰ˆ0.034â€“0.047, p<0.05), contrary to the expectation that ethnocentric consumers prefer local brands only. This novel integration of CSI, IPA, and CETSCALE reveals that even ethnocentric Indonesian consumers are generally satisfied with the Japanese made product, likely due to perceived quality. Findings inform marketing strategies for culturally-branded products.
Keywords: Consumer Satisfaction; Instant Noodles; Japanese Identity; Consumer Ethnocentrism; Semarang.